Guiando almas femininas: a educação protestante da mulher em impressos confessionais no Brasil e em Portugal (1890-1930) - Silva, Sandra Cristina da (2013)
This paper treats confessional printings as a non formal space for the female education. It reflects on the importance of the woman s role to the diffusion of Protestantism in general, and its Presbyterian trend in particular, besides commenting on the proliferation of printings at the First Republic and its relation with education. In this study, Brazilian Northeastern is seen as a relevant space to the diffusion of Protestantism in Brazil; especially on what concerns the relations between Rio Grande do Norte and Pernambuco. Thereby some fountains were fundamental, as the confessional printings, that is, newspapers, magazines, prospects and other materials recollected in archives located in Natal/RN and Recife/PE, and São Paulo. It was also provided a brief incursion on Portuguese confessional printings kept in Oporto, PT. New Cultural History was chosen as theoretic-methodological guide, franchising ways inside the history of book and reading with the help of concepts like Interdependence, Social Configuration (ELIAS, 1993, 1994) and Representation (CHARTIER, 1990), considering that the survey worked out culture-manufactured products that is, intentional materials. It is well known that publishing, or better, the dissemination of printed material used to be associated to Protestants missionary practices since Reform began and, as what concerns the investigated period, in Portuguese and Brazilian lands indistinctly. Printing material in general books, booklets, fragments, as well as the press itself played a central role in divulging reformed ideas, their social options and the means of being and intervening in the world. In this regard, the confessional printings established themselves as an educative, although non schooled, informal space, but, all considered, relevant, seen that they dialogue with another important demand of that social group: formal, literate education. Because it dealt with the diffusion of a printed culture supported by the written word, it required of that group a different modus operandi: formal education. The first letters schools at first, then the high schools later represented spaces established for the circulation of printing material in order that they should be read, divulged and comprehended. This survey intends at last to take a look at Protestantism which, in this context of self-affirmation, reserved a specific place to woman by working out a non formal educational proposal disseminated by printing material. Three models were highlighted in the reformed proposal: Christian education in itself, household education, whose references of motherhood and care towards the neighbor were present and, at last, education to the public space, with emphasis on the practice of teaching. This study also offers a brief dialogue between Brazil and Portugal because, when some periodic printing, book or something like that got to be published in one margin of the Atlantic Ocean, the other margin surely was affected by that feat, received it, divulged it, corroborating the argument in support of the circulation of these printings. It was not only the same language that survived in both maritime coasts; some protestant specificities also crossed out along that sea